BEST INTEREST FOR CHILDREN IN PERMA NO. 5 OF 2019 CONCERNING GUIDELINES FOR TRYING DISPENSATION MARRIAGE APPLICATION CASES - Qurratul Uyun Uyun; Maida Hafidz; Madah Rahmatan (Universitas Islam Indonesia, 2023)
Child marriage has a negative impact on individuals and the environment. Children who marry at an early age do not get the rights they should have so that, which has an impact on divorce and domestic violence due to the unpreparedness of children in building a household; things like that can also affect social structure and order in society, which ends in threats to children's welfare. Children with welfare problems need protection and guidance like children of the same age. The type of research used is library research. The descriptive-qualitative method uses a theoretical approach and facts through the information media, judge's decisions, articles and other sources. The results of the study show that the best interests of the child in PERMA No. 5 of 2019 are all actions that must be considered to ensure the protection, care, welfare, survival and development of children, including efforts to help prosper the growth and development of children and improve family life.